Reproductive technologies in farm animals - Gordon, Ian , 1928- (CABI Publishing, 2017)
Building on the successful structure of the first edition, the second edition of Reproductive Technologies in Farm Animals has been totally updated and revised to provide an up-to-date account of the key techniques employed in manipulating reproduction in farm animals, including beef and dairy cattle, pigs, sheep, goats, buffaloes, camelids, horses and poultry.--COVER